'Super‐eruptions' and silicic volcanism from the Yellowstone volcanic field. (18th July 2013) - Ellis, Ben S.; Mark, Darren F.
<x xml:space="preserve">Abstract</x> Yellowstone is perhaps the world's most famous 'super‐volcano' with an explosive history stretching back more than 2 million years and abundant contemporary evidence of a voluminous magmatic system. The first explosive eruption at Yellowstone was the largest, the Huckleberry Ridge Tuff with a volume estimated at 2500 km3 of deposit. However, recent work using high‐precision geochronology has suggested that this 'poster‐child' of super‐eruptions is actually two distinct events separated by at least six thousand years. The geochronological data indicating differences between the constituent parts of the Huckleberry Ridge Tuff is supported by textural, geochemical and isotopic evidence from numerous studies. Advances in both technology and approaches in the sphere of geochronology are allowing for ever more closely spaced events to be temporally resolved; allowing re‐investigation of deposits considered to represent 'super‐eruptions' at much higher resolution. The appreciation that the Huckleberry Ridge Tuff represents two distinct events illustrates that these large, regionally catastrophic events from Yellowstone occurred more frequently than previously thought. Moreover, by being able to better constrain the intervals between super‐eruptions we can investigate the timescales of magma generation during quiescent periods.